Corporate Power and Globalization in US Foreign Policy. - Cox, Ronald W. (Routledge studies in US foreign policy., 2012)
More than a decade into the new millennium, the fusion of corporate and state power is the essential defining feature of US foreign policy. This edited volume critically examines the relationship between corporations and the US state in the development of foreign policies related to globalization. Drawing together a wide range of contributors, this work explores the role of corporations in using US foreign policies to advance the interests of transnational capital in a wide range of contexts, including: how US government policies have contributed to the globalization of production and finance t.